On a Class of Production Functions - Henryk Kierzkowski (Queen's University, Department of Economics, 1972)
In this paper, the author pays close attention to the production process where at the microeconomic level it seems plausible to assume that at the time when a piece of equipment is installed in the firm, there is no or very little room for variations in the factor proportions. However, what seems more reasonable is that at the micro economic level, for any specific type of equipment one may not only assume that the elasticity of substitution is zero or very near zero at the time when the equipment is installed, but that the elasticity of substitution would be greater the longer the period of time has elapsed. This is to say that it is more reasonable to assume that the elasticity of substitution is a variable over time. And the rest of the paper talks about this same concept and uses graphs and diagrams to aid understanding of the user.
Keywords: 330